PENERAPAN SISTEM AKUNTANSI PADA PERUSAHAAN “ROTI BAKAR PANJO” - Tika Permata Asri; Tri Handoyo; Devita Nurwulan; Oon Feryanto (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The research discusses the implementation of sales, purchasing and payroll accounting systems at the Roti Bakar Panjo UMKM company which uses the Moka and Microsoft Excel applications as operational tools. The research was conducted using qualitative methods through interviews and observations. The research results show that in the Moka application there is still a problem of mismatching inventory data with physical conditions and the manual payroll system with Excel becomes less efficient as the number of employees increases. To overcome these obstacles, it is recommended to implement a more integrated application, such as Talenta for the payroll system, as well as improving features in the Moka application to support more accurate and efficient data management. With this step, the company is expected to be able to improve the performance of its accounting system and support sustainable business growth.